Some Statistical Features of the Information Exchange in Social Networks - Kuptsov, M. I.; Minaev, V. A.; Yablochnikov, S. L.; Dzobelova, V. B.; Sharopatova, A. V. (2020 Systems of Signal Synchronization, Generating and Processing in Telecommunications (SYNCHROINFO), 2020)
To create analytical models for disseminating information in social networks, a special technique has been implemented for selected statistics in the network VKontakte (VK). The statistical features of the change in the number of subscribers to social groups in terms of the pageviews are investigated. The classification of the groups of social network users is proposed; their differences and common patterns of mutual transitions are determined.